Mechanical properties and crack propagation law of coal under different CO2 adsorption time - WANG Lei; WU Yuxuan; CHEN Lipeng; WANG Yong; LIAO Zhipeng; YANG Zhenyu (矿业科学学报)
The structural deformation caused by CO2 adsorption has a significant effect on the stability of coal seam. The authors studied the effect of CO2 adsorption time on the mechanical properties of coal and analyzed the variation of mechanical parameters of coal with adsorption time by using the gas-solid coupling test system and the MTS mechanical test system. By using the industrial CT scanning system and 3D reconstruction technology, the authors built a coal crack structure model to clarify the influence of CO2 adsorption time on the crack structure. Through data interaction with the COMSOL simulation software, the authors carried out the fluid dynamics simulation of CO2 in coal to discuss the influence of CO2 adsorption on the crack propagation law of coal. The results show that: ① The stress-strain curves of coal under different CO2 adsorption time can be divided into three stages, with each stage significantly influenced by the adsorption time. Both the peak strength and elastic modulus exhibit a decreasing trend as the adsorption time increases, with a maximum reduction up to 29.82%. The degree of deterioration increases correspondingly but shows a time-dependent characteristic. Between 5 and 7 days, the change in the deterioration effect is only about 0.5%, indicating a stabilization trend over time. ② The CT scan results show that the cracks in coal propagate from the outside to the inside, and this trend is influenced by the CO2 adsorption time, exhibiting a pattern of initially rapid change followed by slower change. At 7 days, the cracking rate and coalescence rate of coal reach 14.03% and 1.59, respectively, indicating that CO2 has a certain damaging effect on the coal structure. ③ The authors carried out migration modeling for CO2 on the representative volume element (REV) of coal. The results show CO2 migrates in coal from the outside to the inside, and there is a stress concentration area between the crack and the matrix, which causes the crack to propagate, resulting in loosened coal structure and reduced load resistance.